2010
DOI: 10.1159/000316098
|View full text |Cite
|
Sign up to set email alerts
|

Ecthyma-Gangrenosum-Like Bullous Pemphigoid

Abstract: Bullous pemphigoid (BP) is a chronic, autoimmune, subepidermal blistering skin disease with varied clinical presentations. Diagnosis is based on the clinical picture, histopathological findings, and direct and indirect immunofluorescence studies. In unclear cases, ELISA or Western blot analysis helps to establish a definite diagnosis by the detection of immunoglobulin G autoantibodies specific for the hemidesmosomal BP antigens BP230 and BP180. We report 3 cases of BP with an as yet not characterized, distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
(39 reference statements)
0
4
0
2
Order By: Relevance
“…Following French national recommendations for the diagnosis of BP [2], immunological tests are recommended but often not necessary for the diagnosis of typical situations. In contrast, BP180 and BP230 ELISA were reported as useful for the diagnosis of atypical BP, especially BP with atypical cutaneous presentation [14] or BP with mucosal lesions that are difficult to distinguish from mucous membrane pemphigoid [11]. However, it was shown that BP230 ELISA may be positive in some cases of mucous membrane pemphigoid and may not replace electronic immunomicroscopy as a definitive discriminant test [15,16].…”
Section: Commentmentioning
confidence: 99%
“…Following French national recommendations for the diagnosis of BP [2], immunological tests are recommended but often not necessary for the diagnosis of typical situations. In contrast, BP180 and BP230 ELISA were reported as useful for the diagnosis of atypical BP, especially BP with atypical cutaneous presentation [14] or BP with mucosal lesions that are difficult to distinguish from mucous membrane pemphigoid [11]. However, it was shown that BP230 ELISA may be positive in some cases of mucous membrane pemphigoid and may not replace electronic immunomicroscopy as a definitive discriminant test [15,16].…”
Section: Commentmentioning
confidence: 99%
“…IIF studies, ELISAs or Western blot) [1,2,[6][7][8][9] , the presence of a seroreactivity should always be interpreted according to the clinical context and the results of DIF studies (the only exception is gestational pemphigoid, in which strong positive BP180 ELISA values may replace DIF studies [10] ). In patients with atypical clinical findings, such as those reported by Geiss Steiner et al [3] , in our view the presence of circulating autoantibodies by either ELISA or IIF studies does not allow to make a diagnosis of BP if DIF microscopy studies are negative. Nevertheless, these cases have at least the merit to remind us of the importance to consider a non-bullous, 'atypical' variant of an AIBD in elderly patients with chronic itchy skin disorders, even in those in whom almost nothing else suggests this diagnosis a priori.…”
mentioning
confidence: 51%
“…In this issue of Dermatology, Geiss Steiner et al [3] report 3 elderly female patients with a long history of widespread fibrinonecrotic ulcerations on the trunk and the limbs. Unexpectedly, some immunopathological findings suggested a diagnosis of BP.…”
mentioning
confidence: 99%
“…According to our results concerning BP, DIF microscopy seems to be a useful diagnostic method for definitive diagnosis. In a study of Libsker and Borradori (8), authors evaluated atypical variants of BP which were described by Geiss Steiner et al (9). Author's view about these atypical variants was that the presence of circulating autoantibodies by either ELISA or indirect IF studies did not allow to make a diagnosis of BP if DIF microscopy is negative (8).…”
Section: Discussionmentioning
confidence: 99%